Analisis Miskonsepsi Guru dalam Penerapan Profesionalisme dan Etika Pembelajaran - Ninda Amelia Rozana; Uswatun Khasanah; Aqilla Daffa Azzahra; Nita Yuli Astuti (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This article analyzes teachers' misconceptions in interpreting professionalism and learning ethics and their impact on the quality of the learning process. This study evaluates how misunderstandings about professionalism are often reduced to mere administrative compliance and certification acquisition, as well as misconceptions about ethics that are narrowed down to mere politeness without considering moral responsibility, fairness, and objectivity in learning interactions. Through a literature review approach, this study examines various scientific literature to show how these misconceptions affect the effectiveness of knowledge transfer and the development of teachers' pedagogical competencies. The findings show that misunderstandings occur not only among students but also among teachers, even those who are certified, because certification is not yet fully capable of changing mindsets and pedagogical practices. This situation points to the importance of strategies to strengthen professionalism through improving academic standards, implementing training or Continuing Professional Development (CPD), active involvement in professional organizations, and the application of mentoring and coaching. Overall, this analysis confirms that strengthening teacher professionalism and ethics is an urgent need to realize meaningful and fair learning.